ROLAND BARTHES SEMIOTIC ANALYSIS OF THE FILM POSTER “LOOK BACK” - Ananta, Mauralita Dwi; Mochammad Hirsyam Alifiyan Ma’arif; Pungky Febi Arifianto (SNADES, 2025)
Movie posters function as complex visual texts that promote and communicate essential messages to audiences. This study analyzes the poster for the film "Look Back," released on June 28, 2024, in Japan and July 31, 2024, in Indonesia. The film adapts the popular one-shot manga by Tatsuki Fujimoto, chronicling the creative and emotional journey of two young manga artists, Fujino and Kyomoto. The high level of fan enthusiasm for the film highlights the importance of understanding how posters construct narratives. The purpose of this study is to identify and interpret the visual and verbal meanings of the "Look Back" movie poster using Roland Barthes’ semiotic analysis. The research method used is descriptive qualitative, where the poster is examined through three stages: denotation (literal meaning), connotation (associative and cultural meaning), and myth (larger ideological narrative). The results show that the poster effectively presents the visual of a teenage girl focused on working at her desk in a realistic and engaging bedroom setting. By emphasizing the main characters, activities, and background details such as personal belongings, layout, color choices, and the vibe created, the poster implicitly or explicitly conveys the film’s major ideas and themes.